Licorice in nephropathy treatment: phytochemical compositions and pharmacological mechanisms - Feng, Ya-Long; Shui, Le; Jiang, Yin-Xuan; Wang, Yan-Ni; Chen, Lin; Chen, Hua; Wang, Wen-Bo (Frontiers in Pharmacology, 2025)
Nephropathy refers to a wide range of kidney dysfunction and is a highly prevalent condition worldwide, often associated with several disorders, including inflammation, oxidative stress, apoptosis, epithelial-mesenchymal transition (EMT), autophagy, and the deposition of extracellular matrix (ECM). Licorice has been used in China for thousands of years to treat nephropathy, while the underlying mechanisms are still unclear. The triterpenoid and flavonoid compounds are the main components of licorice. The main bioactive components of licorice against nephropathy are glycyrrhizic acid, glycyrrhetinic acid, isoliquiritigenin, glabridin, isoliquiritin and licochalcone A. These components alleviate kidney injury through anti-inflammatory, anti-oxidative stress, anti-apoptosis, promoting autophagy, inhibiting EMT, and reducing ECM deposition by targeting the signaling pathways of NF-κB, TGF-β1, JNK, MAPK, p53, STAT3 and HMGB1. This review will provide a new insight to clarify the bioactive components of licorice against nephropathy and their corresponding mechanisms, which aims to provide useful information for the further application of licorice.